Meal Supervision During Medical Hospitalization for Eating Disorders. (August 2017) - Kells, Meredith; Schubert-Bob, Pamela; Nagle, Katharine; Hitchko, Louise; O'Neil, Kathleen; Forbes, Peter; McCabe, Margaret
The focus of medical hospitalization for restrictive eating disorders is weight gain; however, no guidelines exist on how to achieve successful and safe weight gain. Meal supervision may be a supportive intervention to aid in meal completion and weight gain. The aim of this study was to examine the effect of standardized meal supervision on weight gain, length of stay, vital signs, electrolytes, and use of liquid caloric supplementation in hospitalized adolescents and young adults with restrictive eating disorders. A chart review compared patients who received meal supervision from admission through discharge to an earlier cohort who received meal supervision as needed. There were no differences in weight, electrolytes, or vital signs between the two cohorts. Length of stay for those who received meal supervision from admission was 3 days shorter than earlier cohort. Nursing supervised meals beginning at admission may shorten length of stay and decrease health care costs.